2021
DOI: 10.1017/s0031182021000536
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization ofCysticercus tenuicollisisolates from sheep in the Nile Delta, Egypt and a review onTaenia hydatigenainfections worldwide

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 160 publications
1
7
0
Order By: Relevance
“…In total, 45 datasets describing T. multiceps infections in 11 191 dogs worldwide were revealed during our search, and 639 dogs have been found infected resulting in a pooled global prevalence of 5.8% (95% CI 4.7–6.9%). The prevalence and infection intensities of T. multiceps in dogs are in general lower than that of Taenia hydatigena (Wang et al , 2006; Abbas et al , 2021). Dogs can develop immunity and become refractory to T. multiceps infections after the second or the third reinfections (Willis and Herbert, 1984).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 45 datasets describing T. multiceps infections in 11 191 dogs worldwide were revealed during our search, and 639 dogs have been found infected resulting in a pooled global prevalence of 5.8% (95% CI 4.7–6.9%). The prevalence and infection intensities of T. multiceps in dogs are in general lower than that of Taenia hydatigena (Wang et al , 2006; Abbas et al , 2021). Dogs can develop immunity and become refractory to T. multiceps infections after the second or the third reinfections (Willis and Herbert, 1984).…”
Section: Resultsmentioning
confidence: 99%
“…This was because dogs had access to pastures that were being grazed by goats and sheep and hence can contaminate pastures with their fecal matter. The overall prevalence of 35.4 and 23.3% observed in goats and sheep respectively in this study was comparable to what has been observed among goats and sheep in Pairaba, Brazil of 39% in goats and 17.4% in sheep (de Morais et al, 2017) and in Ceara of 26.2% in goats and 35% in sheep (Soares et al ., 2012) and in Uttar Pradesh, India of 27.3% in goats and 37.2% in sheep (Pathak and Gaur, 1982); in Soroti, Uganda of 42.5% in sheep and 33.3% in goats (Nyero et al ., 2014) and in Nile Delta, Egypt of 21% in sheep (Abbas et al ., 2021). More high prevalence rates have been observed among goats (53%) and sheep (79%) in eastern Ethiopia (Sissay et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Much lower prevalence had been observed in north India of 4.8% in goats and 2.2% in sheep (Singh et al ., 2015), northeast Tunisia of 8.9% in goats and 2.2% in sheep (Khaled et al ., 2020) and northwest Iran of 8.9% in goats and 2.8% in sheep (Mirzaei and Rezaei, 2015). Cysticercus tenuicollis though not zoonotic does not cause serious health effects in goats and sheep but have been found to lower their productivity (Soares et al ., 2012; de Morais et al, 2017; Abbas et al ., 2021). Therefore dogs should be dewormed to get rid of adult cestode worms which shed their eggs in dogs’ feces thereby contaminating pasture grazed by livestock.…”
Section: Discussionmentioning
confidence: 99%
“…The disease can cause economic losses, and its prevalence varies among poor and developing countries (Hama et al., 2018; Sgroi et al., 2020). Cysticercosis has been documented in old‐aged sheep and goats worldwide (Al‐Mayali, 2005; Abbas et al., 2021), but it is considered rare in young lambs (Al Salihi et al., 2016).…”
Section: Introductionmentioning
confidence: 99%